2021
DOI: 10.35848/1347-4065/ac1fb9
|View full text |Cite
|
Sign up to set email alerts
|

Selection criteria of piezoelectric materials for double-parabolic-reflectors ultrasonic transducers (DPLUS) for high-power ultrasound

Abstract: To suit double parabolic reflectors wave-guided ultrasonic transducer (DPLUS) for high-power ultrasound applications, we investigated the selection criteria of piezoelectric materials for DPLUS. Four piezoelectric materials were prepared: two lead–zirconate–titanate (PZT) types and two lead-free types. For non-resonant excitation of the DPLUS waveguide, the piezoelectric constant e and the thickness of piezoelectric materials are two important evaluation indexes. PZT 5H was found as the best candidate. For res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…We had studied DPLUS with ~40 mm long thin waveguide (made of duralumin A2017) in order for understanding the working principle and exploring the excitable vibration amplitude in the thin waveguide [15][16][17]. Results showed that ~7 m/s of vibration velocity amplitude could be realized in the thin waveguide and acoustic pressure in water of over 7 MPa (spatial peak temporal average intensity of ~1.6 kW cm $ ⁄ ) between 1 to 2 MHz could be estimated under the resonant excitation of the thin waveguide [15], thus indicating the highpower performance of DPLUS.…”
Section: A Dplus With a Long Fused Quartz Thin Waveguidementioning
confidence: 99%
“…We had studied DPLUS with ~40 mm long thin waveguide (made of duralumin A2017) in order for understanding the working principle and exploring the excitable vibration amplitude in the thin waveguide [15][16][17]. Results showed that ~7 m/s of vibration velocity amplitude could be realized in the thin waveguide and acoustic pressure in water of over 7 MPa (spatial peak temporal average intensity of ~1.6 kW cm $ ⁄ ) between 1 to 2 MHz could be estimated under the resonant excitation of the thin waveguide [15], thus indicating the highpower performance of DPLUS.…”
Section: A Dplus With a Long Fused Quartz Thin Waveguidementioning
confidence: 99%